1982
DOI: 10.2503/jjshs.50.487
|View full text |Cite
|
Sign up to set email alerts
|

Salt Tolerance of Green Soybeans as Affected by Various Salinities in Sand Culture

Abstract: SummaryGreen soybeans (Glycine max. Merr.) were grown in sand to determine the salt tolerance affected by salinization of sea water, NaCI, Na2504, MgC12 and Mg5O4 at osmotic potentials of -1.20, -1.70 and -2.70 bars as compared to a control of -0.70 bars of base nutrient solution. Dry weight of the whole plant, fresh weight of seeds and pods, and number of pole were greatest in the control and decreased in each salinity with decreasing osmotic potentials. Growth was greatest in the Mg504 series, less in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
1
4
1
Order By: Relevance
“…This result in muskmelons did not agree with data from green soybeans, where CI depressed the growth more than SO4 and Mg did not show an adverse effect (12). This may be due to genetic difference, as observed by other investigators (2,3,13).…”
Section: Discussioncontrasting
confidence: 54%
“…This result in muskmelons did not agree with data from green soybeans, where CI depressed the growth more than SO4 and Mg did not show an adverse effect (12). This may be due to genetic difference, as observed by other investigators (2,3,13).…”
Section: Discussioncontrasting
confidence: 54%
“…Clark 63 was the most sensitive cultivar to increased Cl − at the 8.5 dS m −1 salinity level, and Lee was the least sensitive cultivar. Nukaya et al. (1982) reported that Cl − salt had the greatest detrimental effect on growth and yield in green soybean, when isoosmotic concentrations of different salts were used.…”
Section: Discussionmentioning
confidence: 99%
“…Plants were supplied with 50 ml of sterilized water until they were thinned to one plant per pot 10th days after sowing. Then, they were supplied with 150ml of nutrient solution (Nukaya 1982) every 4 days and with 150ml sterilized water every other day, in a growth chamber (30*C daytime/20~ night) from August to October.…”
Section: Methodsmentioning
confidence: 99%